Model of the communication structures - Лємєхов, Юрій Олександрович (Technology audit and production reserves, 2012)
The article describes the results of a study ways to calculate the parameters of high-frequency communication devices in means infocommunications.The proposed Criteria evaluation of the effectiveness of algorithms and mathematical models defined classes communicator’s structures